Primer izboljšave trajnostnega ravnanja z naravnimi viri: vgradnja volumetričnih vodomerov s sistemom daljinskega odčitavanja v podjetju Kraški vodovod Sežana d.o.o. - Kavre, Vesna; Rozman, Tomislav (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
The purpose of the article is to analyse the effects of installation of the remote reading volumetric water meters in Kraški vodovod Sežana d.o.o. The first part explains notions needed for better understanding of contents, water consumption measuring and remote reading system. The second part of the article presents preparation and analysis of the research. The main result of remote reading volumetric water meters establishment were positive changes and the satisfaction of the management, employees and users. Volumetric water meters are significantly more accurate than multi jet water meters. Remote reading enables faster water meter reading. The system also detects leakages, which reduces water waste and so the company contributes to efficient usage of potable water resources. The results can be used by companies to improve understanding of advantages and disadvantages of the remote reading volumetric water meters installation for the company. Furthermore, the results can be used for further improvement of the system and work processes in the company. Target group are also other organizations in this branch that are just preparing or deciding to introduce the remote reading system. The research not only showed advantages and disadvantages of this system, but it also showed difficulties companies are faced with when initiating the remote reading.